Human Computer Interaction’s insights into the Recognition of Love: A Comprehensive Framework - Ocana Flores, Hernan Isaac (Tierra Infinita, 2023)
This framework considers complex emotions that can be analysed by various current technological techniques, measures, and resources available nowadays. The author postulates an evolving feedback mechanism between man’s psyche and technology development which defines man’s psychological condition as well. The dimensions of the dynamic feedback loop comprise of affective communication via technology, recognition of emotions through technology, and moderation of emotions using technology. Thought the exploration of love other possibilities for theoretical frames of system development, and systems’ needs for other emotions. Using emotion recognition technology (e.g., facial expression analysis) and sentiment analysis, these devices can recognise the users’ emotions, thereby making it possible for designers to develop user-centred designs. What makes emotional technologies exist is the requirement of combining the technologies which are highly precise and can understand the complicated traits of life. Finally, the importance of emotional technologies advancements is discussed as t is now essential to unify these technologies to reach unprecedented accuracies and studying the highest complexity of life phenomena.